ORGANIZATIONAL CULTURE, POSITION PROMOTION AND ENVIRONMENT TO WORK SPIRIT - Tehubijuluw Zacharias; Samson Laurens; Derek Bakarbessy (JURNAL BADATI, 2024)
Morale is a person's desire and sincerity to do his job well and be disciplined to achieve maximum work performance. Therefore, every organization must strive in such a way that its employees still have high morale in completing the assigned tasks. However, to achieve the desired work spirit is not easy, because many factors influence it, including organizational culture, work environment and promotions. This study aims to analyze the influence of organizationalculture, job promotion and work environment either partially or simultaneously on work morale. This research uses descriptive-quantitative approach with causal correlational type. The population used in this study were all employees of the Planning and Development Agency of Maluku Province as many as 134 people consisting of 74 ASN and 60 honorary staff. Determination of the number of samples using the Isaac and Michael sample table, where if the population is 134 people, then at the 95% confidence level, the sample is 97 people, which is determined by simple random sampling. Data were analyzed by multiple linear regression. The results of the study concluded that organizational culture, promotion and work environment had a positive andsignificant effect on work morale, either partially or simultaneously.